Thematisches Verzeichnis der musikalischen Werke von Wolfgang Amadé Mozart Köchel-Verzeichnis (KV) - Köchel, Ludwig von 1800-1877; Zaslaw, Neal -1939; Leisinger, Ulrich 1964-; Pfadt, Miriam; Geanta, Ioana 1982-; Internationale Stiftung Mozarteum (Wiesbaden Breitkopf & Härtel, 2024)
Ludwig Ritter von Köchel presented the first edition of a chronological catalog of Wolfgang Amadé Mozart’s works with Breitkopf & Härtel in 1862 – a milestone in music research. In order to present the rapidly growing knowledge of all aspects of Mozart’s oeuvre, several new editions were subsequently published. It was believed that new findings on chronology should also be reflected in new work numbers. The resulting number construct with countless cross-references became increasingly complicated and ultimately failed to gain acceptance either in Mozart research or in musical practice.The new edition, which appears for the first time under the name Köchel-Verzeichnis, goes back to the original numbering without maintaining the claim to chronological order. A clear concordance provides clarity. The long-standing collaboration between Neal Zaslaw and the International Mozarteum Foundation guarantees a catalog of works that is up to date and offers a reliable overview of W. A. Mozart’s oeuvre.
Thematic Catalog of the Musical Works of W. A. Mozart
Vorwort und "Hinweise zu Anlage, Inhalt und Benutzung" in Deutsch und Englisch; eigentliches Verzeichnis deutsch
bearbeitet von Neal Zaslaw ; im Auftrag der Internationalen Stiftung Mozarteum vorgelegt von Ulrich Leisinger ; unter Mitwirkung von Miriam Pfadt und Ioana Genata
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Catalog